2018
DOI: 10.1108/itse-02-2018-0015
|View full text |Cite
|
Sign up to set email alerts
|

A multi-modal study into students’ timing and learning regulation: time is ticking

Abstract: How to cite:Tempelaar, Dirk; Rienties, Bart and Nguyen, Quan (2018). A multi-modal study into students' timing and learning regulation: time is ticking. Interactive Technology and Smart Education, 15(4) pp. 298-313.For guidance on citations see FAQs. ' (Schumacher and Ifenthaler, 2018, p. 397). The use of multi-modal data, which is characterised by two or more distinct types of data, offers new insights into long-standing academic debates that have been addressed in the past with empirical studies based on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…[36,52,58,80]. Numerous studies explored relations between trace data, performance and SRL using self-reports [30]; some in combination with other theories, for example theories of motivation [20] socio-cultural perspectives [31], Self-Determination Theory and the Control-Value Theory of achievement emotions [86][87][88]. 5.…”
Section: Table 2 Blended Learning Definitionsmentioning
confidence: 99%
“…[36,52,58,80]. Numerous studies explored relations between trace data, performance and SRL using self-reports [30]; some in combination with other theories, for example theories of motivation [20] socio-cultural perspectives [31], Self-Determination Theory and the Control-Value Theory of achievement emotions [86][87][88]. 5.…”
Section: Table 2 Blended Learning Definitionsmentioning
confidence: 99%
“…Dispositional learning analytics (see [26]), on the other hand, seeks to combine digital trace data (e.g., those generated by engagement in online learning activities) with learner data (e.g., dispositions, attitudes, and values assessed via self-report surveys). By doing so, recent research has found that learning dispositions (e.g., motivation, emotion, self-regulation) strongly and dynamically influence engagement and academic performance over time (e.g., [2729]). In addition, this research suggests that the predictive value added by consideration of learner data might be time-dependent: learner data seems to play a critical role up until the point that feedback from assessment or online activities becomes available.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed recent research has highlighted that on a more micro-level learners at the OU have substantially different learning needs and ambitions (Law, 2015;Li et al, 2017), depending on a complex interplay of affective (Hillaire et al, Submitted;Tempelaar et al, 2018b), behavioural (Chua et al, 2017;Rets, 2018;Rizvi et al, 2018), and cognitive factors, as well as socio-economic and demographic factors (Richardson, 2015). Therefore, in the remainder of this chapter we will primarily focus on how to provide more personalised and individualised support for learning in the next 2-5 years.…”
Section: Discussionmentioning
confidence: 99%
“…(Herodotou et al, 2017(Herodotou et al, , 2019Hlosta et al, 2015). Furthermore, some institutions like Universiteit van Amsterdam (Berg et al, 2016), University of Keele (de Quincey et al, 2019), and Maastricht University (Tempelaar et al, 2018b) have successfully experimented with providing learning analytics data directly to students in order to support their learning processes and self-regulation.…”
Section: Introductionmentioning
confidence: 99%